When the whip comes down: Marxism, the Soviet experience, and the nuclear revolution. (22nd May 2017) - Craig, Campbell
Abstract: This article examines the conflict between traditional Marxist attitudes toward war and the problem of the nuclear revolution. It shows how the advent of the nuclear revolution in the 1950s undermined traditional Marxist-Leninist concepts of war, and then goes on to argue that this development must be placed at the centre of contemporary Marxian IR if it is to have explanatory power in the twenty - first century. To make this case directly, it engages with Justin Rosenberg's revival of Trotsky's idea of uneven and combined development and its subsidiary law of 'the whip of external necessity', and argues that the whip can remain salient today only if one accepts the political utility of nuclear war. The impasse created by the nuclear revolution, it concludes, points Marxist IR in the direction of classic Marxist visions of supranationalism and human unity.